Introduction: State capacity and elections in the study of authoritarian regimes. Issue 1 (January 2018) - Croissant, Aurel; Hellmann, Olli
Studies of multiparty elections in authoritarian regimes have proliferated in recent years. Nevertheless, the available evidence remains inconclusive in terms of when, where, or why elections work to sustain or undermine authoritarian rule. The contributions to the special issue 'State Capacity, Elections and the Resilience of Authoritarian Rule' argue that analyzing the extent to which the effect of elections on authoritarian regime resilience is mediated through the factor of state capacity helps to solve this puzzle. This introduction lays out the analytical foundation for this discussion by reviewing key terms and concepts, and by highlighting possible theoretical connections between the state capacity literature on the one hand and the electoral authoritarianism literature on the other. Furthermore, it considers the contributions in this special issue, and points out areas of agreement and disagreement between the authors, while simultaneously placing the different arguments within the broader field of enquiry.